Instilling Self-Confidence Character in Siminal Siminul Dance Learning at Merpati Blora Course and Training Institute - Hartono Hartono; Putri Gisa Harum Rahayu (Universitas Negeri Semarang, 2023)
Self-confidence for early childhood is still minimal, especially when it comes to interact with the surrounding environment. The lack of self-confidence indication appears in Siminal Siminul Dance learning at LKP Merpati Blora, which the children feeling shy and afraid to perform in public following by the lack of courage to express their opinions. The purpose of the study was to analyze the Instilling of self-confidence character in Siminal Siminul Dance learning at LKP Merpati Blora. The method used in the research was a qualitative method with a phenomenological approach. Data collection techniques using observation, interviews and documentation. Data validity techniques used triangulation of sources, methods and theories while data analysis uses data reduction, data presentation and conclusion drawing. The results showed success in instilling self-confidence through 4 indicators at LKP Merpati Blora in learning Siminal Siminul Dance, namely, believing in one's own abilities resulted the students experiencing changes from 6 students to 20 students. Independent in making decisions aimed at success with changes from 9 students to 20 students. Positive thinking resulted in changes from 6 students to 20 students and the courage to express opinions from 6 students to 16 students. The results of this study are expected to be literature to add insight for the readers regarding the benefits of dance learning to increase children's self-confidence.